2014
DOI: 10.1111/cup.12287
|View full text |Cite
|
Sign up to set email alerts
|

Pulse granuloma of the lip: morphologic clues in its differential diagnosis

Abstract: Pulse granuloma is not a common condition in cutaneous pathology. In diagnosing this condition, it is essential to determine if the foreign fragmented bodies are really vegetable parts. Certain vegetable structures, such as hyaline rings, have been clearly emphasized in the literature. However, other vegetable parts can show certain morphologic similarities with animal structures, especially if observed in a fragmented biopsy, as is the case with the pericarp (which can mimic the cuticle of a maggot) or the en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…10 Harrison and Martin 11 have shown that the pathogenesis is related to the persistent cell wall as an etiologic factor. 32 In our case, there was no systemic or localized reason for the occurrence of the pulse granulomas. No special stain is useful in the diagnosis of pulse granulomas.…”
Section: Answermentioning
confidence: 44%
“…10 Harrison and Martin 11 have shown that the pathogenesis is related to the persistent cell wall as an etiologic factor. 32 In our case, there was no systemic or localized reason for the occurrence of the pulse granulomas. No special stain is useful in the diagnosis of pulse granulomas.…”
Section: Answermentioning
confidence: 44%
“…The analysis under polarised light microscopy is useful in distinguishing plant from animal elements, however some animal structures may show the birefringent properties. On the other hand, the presence of animal structures is mainly related to oral or cutaneous myiasis, but rarely associated with internal infections [18]. Several studies have demonstrated that hyaline rings are residues of plant material and can be of various morphology: roughly ovoid, circular structures; hyaline rod-like shaped structures; hyaline masses lying within the fibrous connective tissue stroma with small calcified basophilic bodies; clearly identifiable plant cells; and metaplastic bone formation [12, 18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the presence of animal structures is mainly related to oral or cutaneous myiasis, but rarely associated with internal infections [18]. Several studies have demonstrated that hyaline rings are residues of plant material and can be of various morphology: roughly ovoid, circular structures; hyaline rod-like shaped structures; hyaline masses lying within the fibrous connective tissue stroma with small calcified basophilic bodies; clearly identifiable plant cells; and metaplastic bone formation [12, 18, 19]. Philipsen and Reichart [2] suggested that ring-like structures were formed during degradation of plant material by host phagocytic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although pulse granuloma is usually described in the posterior areas of the mandible in relationship to previous periodontal surgery, a dermatopathologist may also find them in perirectal biopsies, as well as in lip biopsies …”
Section: Alimentary Detritusmentioning
confidence: 99%
“…If only some parts of the maggots are found in an oral biopsy, there is a chance of misdiagnosis of pulse granuloma . In this respect, we have performed immunohistochemical studies on maggots.…”
Section: Maggotsmentioning
confidence: 99%